Implementation of Guided Discovery Learning Method Using Student Worksheets to Improve Physics Learning Outcomes on Light Reflection Material - Azomi, Ruhul; Tsamarul Hizbi; Edi Eko Wahyudi (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
The purpose of this study was to determine the achievement of the application of the guided discovery method with student worksheets on the completeness of physics learning outcomes of class VIII students of MTs NW BW 2 Rensing. This type of research is classroom action research (CAR) which is carried out in two cycles. The techniques used in data collection are learning outcome evaluation techniques and observation techniques. Data analysis techniques with student activity analysis techniques and average student activity scores and learning outcome analysis techniques with learning completeness and average learning achievement. The results of the study were obtained in cycle I, the average score of student activity in the first meeting was 2.8 categorized as quite active, the second meeting was 2.9 categorized as quite active, learning completeness was obtained by 73% with an average test score of 69.17 with the number of students who completed 17 people. In cycle II, the average score of student activity in the first meeting was 3.3 categorized as quite active, the second meeting was 3.56 categorized as active, the completion of learning outcomes was 86.95% with an average test score of 73.04 with the number of students who completed 20 people. From the results of data analysis, it can be concluded that the application of the guided discovery learning method using student worksheets can improve the completion of physics learning outcomes in the material on light reflection of class VIII of Madrasah Tsanawiyah Nahdatul Wathan Birul Walidain 2 Rensing East Lombok.